IMPROVING MENTAL HEALTH CARE ACCESS, ENGAGEMENT, AND DELIVERY AMONG DIVERSE, UNDERSERVED POPULATIONS. (11th November 2018) - Jimenez, D; Conwell, Y
Abstract: It is well-established that racial/ethnic minority older adults, and other underserved groups, including older adults with severe mental illness, have unmet need for mental health care. Mental health services researchers use a variety of methodologies, such as surveys, interventions, qualitative interviews, and large-scale data analytic techniques, to better assess this unmet need for care, as well as to identify and implement methods to improve access to, engagement in, and delivery of high quality care. This session will highlight some of the truly exceptional and diverse work that has been done in the area of geriatric mental health services research. Using mental health services research methodology, speakers will present data on disparities in mental health care, prevention of mental illness, health promotion, and technology. Particular attention will be paid to the diversity of methods mental health services researchers employ in order to address the diverse and complex mental health needs of older adults.